Cost competitiveness of Chinese and Finnish chemical industries - Enjing Li; Paavo Suni; Yanyun Zhao (The Research Institute of the Finnish Economy (ETLA), 2008)
This study focuses on the labour cost competitiveness of the chemical industries in China and Finland in particular, using the corresponding German, the US and Estonian industries as a point of comparison in the early 2000s. This study deepens the analysis of the earlier study of the cost competitiveness of the manufacturing industries in the same group of countries. Separate studies focusing on the labour cost competitiveness are carried out in a parallel manner on the fabricated metal industries and paper industries. The results of these three sector studies deepen the knowledge about the change of competitiveness and its level. Large unit labour cost differences in a common currency were obviously a key factor behind exceptionally rapidly changing international production and trade structures in the late 1990s and early 2000s. The Chinese chemicals and chemical products and rubber and plastic products industries grew by 21 and 23 per cent per year in 2000-2007 as the average annual growth of the value added of world manufacturing volume was only 3 per cent in 2000-2006. Nominal wages as such do not imply good international competitiveness. Chinese wages are, however, low even if the Chinese low labour productivity is taken into account and costs per unit of production are compared in a common currency. The relative levels of the Chinese unit labour costs vis-à-vis Germany, using the unit value ratios (UVR) to make the production volumes comparable, were estimated to be about 6 and 2 per cent in the chemicals and chemical products and rubber and plastic products industries, respectively. In the case of the chemicals and chemical products industry, the ratio has even declined in the course of the 2000s, while in the rubber and plastic products industry it has been stable. Improving labour productivity in China had compensated for the effects of rapidly rising wages and an appreciating Renminbi Yuan in the case of the chemicals and chemical products industry and it had even more than compensated for it in the case of the rubber and plastic products industry.
Keywords: 330; competitiveness; unit value ratio; UVR; chemical industry; NACE 24; NACE 25; Chemieindustrie; Arbeitsproduktivität; Arbeitskosten; Internationaler Wettbewerb; China; Finnland